Intra-party democracy index: a measure model from Brazil - Salgado, Eneida Desiree (2020)
Political parties are, by constitutional force, essential to Brazilian democracy, and equally necessary for the composition and functioning of republican institutions. The 1988 Brazilian Constitution also determines, from a systemic reading, that political parties should be internally democratic. Thus, the present work seeks to develop an intra-party democracy index from the Brazilian experience, considering the fields of Political Science and Electoral Law. The methodology used consisted in the analysis of the statutes of the political parties registered in Brazil until 2018, based on a series of variables, developed from the constitutional and legal norms and principles applicable to the parties, by the reading of the specialized literature, which were translated into questions, whose respective answers were transformed into data, presented as tables, which present the degrees of internal democracy of the Brazilian political parties. The results obtained indicate a low level of internal democracy in the parties, with little use of democratic mechanisms for their organization and decision-making. The investigation demonstrated the need to extend the study to concrete party practices, as well as research on how to make the functioning of parties more plural, which was not the subject of the investigation. It is concluded that even after the Brazilian re-democratization, political parties use oligarchic practices, incompatible with the Brazilian Constitution and with the democratic principle itself.